Results-Based Financing in Education : Learning from What Works - Lee, Jessica D. (World Bank, Washington, DC, 2019)
Results-based financing (RBF) has gained popularity in the international development community because of its potential to make education spending more effective and efficient. In the education sector, RBF has been primarily applied to four levels: teachers; students and families; schools; and governments. The results overall have been mixed, with some notable successes and some disappointing experiences. This report explores when and how RBF can help achieve better impacts in education. While there is no rigorous evidence available to suggest that RBF on its own is better at producing learning outcomes relative to other development financing modalities, there is a significant amount of research that shows RBF can have positive effects by incentivizing specific stakeholders in the education system. In addition, there is operational evidence available on how RBF can be designed and implemented with country partners more effectively. It is important for practitioners and policymakers to learn from this evidence as the RBF portfolio in education grows across development agencies.